The Development of “Arum Luhuring Pawiyatan Ing Astanira” As a Part of Scientiﬁc Environment in Conservation Insight at Universitas Negeri Semarang - Tijan, Puji Lestari; Suhardiyanto, Andi; Hermawan , Dwi (KnE Social Sciences, 2019)
Thisstudyaimstoexploretheslogan“Arumluhuringpawiyataningastanira”asaspirit ofconservationatUniversitasNegeriSemarang(UNNES),asthefoundationofbehavior of academic community in campus activity. Explore habits and social capital in support ofconservationspiritimplementationtorealizeaacademicclimate.Thesocialpractice theory of Bourdieu, is the basis of analysis in this qualitative study. This study analyze the social interpretation of “Arum luhuring pawiyatan ing astanira”. Phenomenology approach is used with UNNES academic research subjects such as students, lecturers, and administrative staff. Research ﬁnds; First, the spiritual values of “arum luhuring pawiyatan ing astanira” means that the progress of the university is in the hands of the academic community. However, campus residents have not yet embraced this meaning,especiallyinacademiclife.Second,operationalrulesforimplementing“arum luhuring pawiyatan ing astanira” have not been socialized. Therefore, this spirit is not yetsigniﬁcantincampusactivity.Third,developmentisdonethroughthecurriculumof collegeconservationandethicsofcollegelife.Recommendationsbasedontheresults of the study are the implementation of intensive socialization of the spirit of education inallaspectsofcampusactivitiesinordertoestablishaconservationacademic climate. Keywords: Arum Luhuring Pawiyatan in Astanira, habits, UNNES